2019
DOI: 10.1021/acssuschemeng.9b04930
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Life Cycle Assessment, and Polymerization of a Vanillin-Based Spirocyclic Diol toward Polyesters with Increased Glass-Transition Temperature

Abstract: Bio-based rigid diols are key building blocks in the development and preparation of high-performance bioplastics with improved thermal and dimensional stabilities. Here, we report on the straightforward two-step synthesis of a diol with a spirocyclic acetal structure, starting from bio-based vanillin and pentaerythritol. According to a preliminary life cycle assessment (LCA), the greenhouse gas emissions of this bio-based diol are significantly lower than those of bio-based 1,3-propanediol. Copolymerization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 80 publications
1
57
1
Order By: Relevance
“…The T g and M n of PBSFs compared with poly(1,4‐cyclohexanedimethylene furandicarboxylate) (PCF), 69 PEF, 20,31,66,67,69,70 PPF, 26,28,31 poly(isosorbide cyclohexane dicarboxylate) (PCI), 46 poly(butylene 2,4:3,5‐Di‐O‐methylene‐D‐mannitol terephthalate) (PBManxT), 50 poly(ethylene‐1,4‐cyclohexyldimethylene‐isosorbide terephthalate) (PEICT), 71 poly(isoidide‐2,5‐bismethylene terephthalate) (PXIIT), 72 PHVT, 73 poly(ethylene 1,4‐cyclohexanedione glycerol diketal 2,5‐furandicarboxylate) (PCHDF) 74 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…The T g and M n of PBSFs compared with poly(1,4‐cyclohexanedimethylene furandicarboxylate) (PCF), 69 PEF, 20,31,66,67,69,70 PPF, 26,28,31 poly(isosorbide cyclohexane dicarboxylate) (PCI), 46 poly(butylene 2,4:3,5‐Di‐O‐methylene‐D‐mannitol terephthalate) (PBManxT), 50 poly(ethylene‐1,4‐cyclohexyldimethylene‐isosorbide terephthalate) (PEICT), 71 poly(isoidide‐2,5‐bismethylene terephthalate) (PXIIT), 72 PHVT, 73 poly(ethylene 1,4‐cyclohexanedione glycerol diketal 2,5‐furandicarboxylate) (PCHDF) 74 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…In another piece of work, Mankar et al synthesized a spiro-diol by acetal formation in a reaction of pentaerythritol with two equivalents of vanillin. 25 Incorporation of this rigid spiro-cyclic diol in copolyesters produced from 1,6-hexanediol and dimethyl terephthalate resulted in improved T g and thermal stability. 25 Hence, this gave materials similar to Akestra™, a commercial fossil-based high-performance polyester produced from a spiro-diol, ethylene glycol and terephthalic acid.…”
Section: Introductionmentioning
confidence: 99%
“…25 Incorporation of this rigid spiro-cyclic diol in copolyesters produced from 1,6-hexanediol and dimethyl terephthalate resulted in improved T g and thermal stability. 25 Hence, this gave materials similar to Akestra™, a commercial fossil-based high-performance polyester produced from a spiro-diol, ethylene glycol and terephthalic acid. 26 Using a similar strategy, Warlin and coworkers reported the synthesis of a rigid spirodiol from pentaerythritol and two equivalents of fructosebased 5-hydroxymethylfurfural.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 2,2′-bifuran-5,5′-dicarboxylic acid (BFDCA) can be used as a precursor for novel bio-based polyamides and polyesters [40][41][42]. Derived from furfural, BFDCA is a C10 biheteroaryl monomer useful in the synthesis of new polymers [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%